Tau Acts in Concert With Kinase/Phosphatase Underlying Synaptic Dysfunction - Fan, Xing; Xia, Liye; Zhou, Zheng; Qiu, Yanyan; Zhao, Chenhao; Yin, Xiaomin; Qian, Wei (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is characterized by two pathological features: neurofibrillary tangles (NFTs), formed by microtubule-associated protein tau, and abnormal accumulation of amyloid-β (Aβ). Multiple evidence places synaptic tau as the vital fact of AD pathology, especially at the very early stage of AD. In the present review, we discuss tau phosphorylation, which is critical for the dendritic localization of tau and synaptic plasticity. We review the related kinases and phosphatases implicated in the synaptic function of tau. We also review the synergistic effects of these kinases and phosphatases on tau-associated synaptic deficits. We aim to open a new perspective on the treatment of AD.